Metodologia para análise de sistema de transporte coletivo por ônibus através de indicadores de qualidade - Lança, João Felipe Almeida [UNESP] (2015)
The paper analyzes a proposal to restructure the Public Transport System by bus in Bauru, based on operational research and service image, made in 2013. With those results, the minicipality planned in the medium